A French dandy in New York: Robert de Montesquiou and American visions of France in the Progressive era. (2nd October 2017) - Verhoeven, Timothy
Abstract : This article explores American stereotypes of France in the Progressive era by analysing the little-known visit of Count Robert de Montesquiou. The most famous dandy in fin-de-siècle Paris, Montesquiou arrived in 1903 to give a series of talks on literature. His visit, however, sparked a wave of hostility which reveals the role of gender, and particularly masculinity, in driving francophobia. At the same time, his ability to win an admiring audience attests to the appeal of France. The response to Montesquiou thus illuminates the negative and positive stereotypes which together made up American perspectives of France in this era.